Baskakov‐Durrmeyer type operators involving generalized Appell Polynomials. (22nd December 2019) - Neer, Trapti; Acu, Ana Maria; Agrawal, P.N.
Abstract : In this paper, we define the Baskakov‐Durrmeyer type operators based on generalized Appell polynomials. Here, we establish moment estimates, an estimate via weighted modulus of continuity and a Voronovoskaya type asymptotic result. Further, we study a quantitative‐Voronovoskaya‐type theorem and Grüss Voronovskaya‐type theorem. Lastly, we give the approximation result for functions having derivatives of bounded variation.